Surface-dependent properties of α-Ag2WO4: a joint experimental and theoretical investigation - Laier, Leticia O. [UNESP]; Assis, Marcelo; Foggi, Camila C.; Gouveia, Amanda F.; Vergani, Carlos E. [UNESP]; Santana, Luís C. L. [UNESP]; Cavalcante, Laécio S.; Andrés, Juan; Longo, Elson (Springer Nature, 2020)
Alpha-silver tungstate (α-Ag2WO4) has attracted much attention in recent years due to its unique crystal and electronic structures, which are suitable for a wide range of applications. This work presents a more realistic study, based on first-principles calculations and experimental results, of the potential of α-Ag2WO4 for antibacterial and photocatalytic activity. α-Ag2WO4 material has been successfully synthesized by a coprecipitation method and subjected to microwave irradiation for different times. The as-synthesized microcrystals were structurally characterized by X-ray diffraction, while the morphological aspects were investigated by field emission scanning electron microscopy. The experimental studies and theoretical simulations of α-Ag2WO4, based on density functional theory calculations, have highlighted several key parameters (surface dependent) that determine the antibacterial (against Staphylococcus aureus) and photocatalytic activity (for the degradation of rhodamine B) and provided some general principles for material design. We believe that our results offer new insights regarding the local coordination of superficial Ag and W atoms (i.e. clusters) on each exposed surface of the corresponding morphology, that dictate the antibacterial and photocatalytic activities of α-Ag2WO4, a field that has so far remained unexplored.
Keywords: Antibacterial and photocatalytic activity; Morphology; α-Ag2WO4